Comunicação pública da ciência e health literacy no portal da ANVISA - Bastos Junior, José Carlos (Universidade Federal de São Carlos, 2016)
This study aimed to verify the nature of public health communication practiced on the ANVISA portal, from promotional materials (informative brochures), whose apparent goal is to contribute to the promotion of health literacy (HL) citizens. Additionally, it was found, by applying one websites evaluation script, the quality of information architecture provided by that portal. The methodology was qualitative and qualitative approach. Subsidizing this analysis portal, literature surveys were conducted concerning issues of public communication of science, health literacy, scientific literacy, and soon rescue the institutionalization trajectory of health surveillance policy in Brazil, to understand and situate the creation of ANVISA . We analyzed a total of 12 booklets, evaluated by applying a list of questions (check list), in order to verify in which public communication and types of HL the the same fall. In summary, the results from the analyzes indicated that the predominant public communication model in textbooks is the contextual model, highlighting the materials that are targeted to children and youth. In relation to HL types, it is concluded that the material as a whole contribute to the promotion of functional / HL basic, ie meet the minimum requirements to promote HL.
Keywords: Comunicação pública da ciência; ANVISA; Cartilhas de saúde; Health literacy; Scientific literacy; CIENCIAS SOCIAIS APLICADAS